Influence of the qualitative and quantitative composition of the queen-rearing colony and the number of grafted larvae on the weight of queen bees - Mykola Voinalovych; Valerii Brovarskiy; Ihor Golovetskyi (Тваринництво та технології харчових продуктів, 2022)
The relevance of the study is conditioned by the practical need to determine the optimal number of grafted larvae in the queen-rearing colony when breeding queen bees. The purpose of the study was to investigate the influence of the qualitative and quantitative composition of bees and brood in the queen-rearing colony on the reception of queen larvae and the weight of reared queen bees. The study was conducted using bees of breed Apis mellifera sossimai. To complete the tasks set, control and experimental groups of three bee colonies each were formed. The difference between the control and experimental groups was the different age ratios of bees and the number of open and sealed broods. In each group of colonies, 30, 40, 50, 60 larvae were alternately grafted at a time with an interval of 5 days, the percentage of their reception, the output of queens and their weight were determined by counting the number of larvae that the bees fed and from which the queens came out, and the weight of queens was determined on laboratory scales during the first four hours after leaving the queen cell. A total of 862 queen bees were bred and studied. During the research, it was found that in the colonies of the experimental group, if they were grafted from 30 to 40 larvae, the percentage of their reception was 88.1-86.2%, respectively. Analysing the weight indicators of queens obtained with a given number of grafted larvae, it was found that it was 195.0-197.3 mg, there was no significant difference with the corresponding indicators of the control group. However, with the subsequent loading of queen-rearing colonies in the experimental group with 50 larvae, the percentage of their reception prevailed by 18.2%, and the weight of queens exceeded similar indicators of the control group by 10%. Notably, the average weight of queens in the control group was 176.3 mg, which is 8.7 mg less than the requirements for the weight of infertile queens established by the breed standard. With a further increase in simultaneously grafted larvae in the queen-rearing colony to 60 units, the rate of their admission in the experimental group decreased by 5% and amounted to 80.5%. At the same time, in the control group, larval reception and queen weight decreased to unacceptable levels and amounted to 67.5% and 172.4 mg, respectively. Therefore, by increasing the number of nurse bees and reducing the number of open brood in the queen-rearing colony, better conditions are created for growing high-quality queen bees, which, in turn, allows simultaneously grafting 48% more larvae compared to the conventional method. The results of the study are of practical value for improving the methods of establishing queen-rearing colonies during the artificial breeding of queen bees